Simultaneous saline irrigation during retrograde rigid ureteroscopic lasertripsy for the prevention of proximal calculus migration - Sun, Lu; Peng, Fang-li (Canadian Urological Association Journal, 2013)
Objective: To analyze the clinical efficacy of Simultaneous saline irrigation method in treating upper-mid ureteral stone migration and overall efﬁciency during ureteroscopic lasertripsy. Methods: We prospectively evaluated 78 patients with a total of 95 upper-mid ureteral stones, which were treated with holmium: YAG lasertripsy. These patients were randomized into two groups. In group I (39 cases with 44 ureteral stones), conventional ureteroscopic lasertripsy was performed in like manner. While in group II (39 cases with 51 ureteral stones), the Simultaneous saline irrigation method was used during lasertripsy. There was no significant difference between the groups with regards to stone site, size or state of the upper urinary tract by spiral computed tomography or excretory urography. Data were analyzed regarding stone migration, lengths of time, and ureteral clearing for various stages of each procedure. Results: One patients (2%) occurred upward stone migration in group II, while in group I it occurred in eight patients (20%).The operative time in group I ranged between 35 to 55 minutes (mean, 44.8±5.3), while in group II it ranged between 40 to 69 minutes (mean, 50.4±3), The operative time was no significant difference between the groups (p<0.05). Ureteral perforation, urinoma, and urosepsis were not seen in both groups. Conclusion：Simultaneous saline irrigation method demonstrated a statistically significant advantage over the conventional methods. Operation can be performed persistently under clear vision, and the calculus can not be moved upwards, the fragmentation easily to be flushed out. Our data suggest that this method is simple，safe and effective in preventing proximal stone migration during ureteroscopic lasertripsy.